THE INTRINSIC ELEMENTS IN WILLIAM FAULKNER’S AS I LAY DYING - Manurung, Iqbal Fahruzi; Dewi, Ratna Sari; Sopha, Diana; Nurmala, Dewi (Fakultas Sastra UMN AL Washliyah, 2024)
This study aims to identify the intrinsic elements of the novel As I Lay Dying. The data are from the story As I Lay Dying. This research uses qualitative research method. The results there are some elements found of intrinsic elements. Thereis characterization which is described from the story was Cash Bundren. Then, there is a plot that describe the condition of America in that time. There is a complication relates the Addie’s corpse. Then, there is a falling action that describe the Addie’s buried. Then, there is a climax relates to the Darl’s arrest and leads to the end of the trip and themes relates to the economic conditions in America.